1999
DOI: 10.2214/ajr.172.4.10587120
|View full text |Cite
|
Sign up to set email alerts
|

Endoluminal CT colonography after an incomplete endoscopic colonoscopy.

Abstract: We evaluated the clinical usefulness of endoluminal CT colonography after an incomplete colonoscopy. SUBJECTS AND METHODS. We prospectively studied 40 patients in whom the cecum could not be reached endoscopically despite adequate bowel preparation. Endoluminal CT colonography (120 kVp, 120 mA, 3-mm collimation, pitch of 2, 1.5-mm interval reconstruction) was performed within 2 hr of incomplete colonoscopy. Two-dimensional multiplanar reformatted images and three-dimensional endoluminal images were analyzed. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0
3

Year Published

1999
1999
2008
2008

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(69 citation statements)
references
References 21 publications
1
65
0
3
Order By: Relevance
“…Previous studies on CTC after incomplete colonoscopy have been conducted [6][7][8][9][10] . These studies were inhomogeneous regarding the patients' selection, because they included asymptomatic as well as symptomatic subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on CTC after incomplete colonoscopy have been conducted [6][7][8][9][10] . These studies were inhomogeneous regarding the patients' selection, because they included asymptomatic as well as symptomatic subjects.…”
Section: Discussionmentioning
confidence: 99%
“…In order to complete evaluation of the colon, radiological examinations can be performed such as double contrast barium enema (DCBE) [5] and computed tomography colonography (CTC). In particular, several studies have shown that CTC is a valuable tool to evaluate the proximal colon after incomplete colonoscopy [6][7][8][9][10] , and the American Gastroenterologists Association (AGA) recognized that CTC is indicated for adults with failed colonoscopy [11] . We report the results of CTC systematically performed in subjects with positive FOBT and incomplete colonoscopy in the context of a population-based screening programme for CRC with FOBT.…”
Section: Introductionmentioning
confidence: 99%
“…When an optical colonoscopy cannot be completed, CTC has been shown to allow examination of the area in 90% of the patients (86). A study on 34 patients with clinical suspicion of CRC and 20 patients without suspicion of CRC found that the incomplete optical colonoscopy had a sensitivity and specificity of 56% and 92%, respectively.…”
Section: Incompletion Ratesmentioning
confidence: 99%
“…Virtual colonoscopy has the ability to examine the proximal colon above an obstructing o r impassable lesion. Morrin [15] compared virtual colonoscopy with bariu m enema in 40 patients who had a failed endoscopy. Virtual colonoscopy had significantly better views of all colonic segments and was better tolerated by the patient.…”
Section: Virtual Colonoscopymentioning
confidence: 99%